INVESTIGATION MANUSCRIPT OF EXTRAORDINARY EVENTS (KLB) FOOD POISONING AT SMPN 4 KINTAMANI SONGAN B VILLAGE, KINTAMANI DISTRICT, BANGLI REGENCY, BALI. - Nuhfarizki Lintang Prakasa; I Made Subrata; Nyoman Suardani (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background: An extraordinary event (KLB) of food poisoning is a public health issue that requires a rapid response. On May 14, 2025, several students at SMPN 4 Kintamani reported experiencing acute symptoms of food poisoning after eating in the school cafeteria. This study aims to identify the source, distribution patterns, and environmental factors influencing the incident. Method: This study used a case-control design with a quantitative approach. Subjects consisted of 16 students as cases (having symptoms of poisoning) and 32 students as controls (without symptoms), selected purposively. Data collection was conducted through interviews using a semi-structured questionnaire, environmental sanitation observations, and laboratory examination of water samples. Results: Symptoms appeared 1–26 hours after food consumption, indicating a point source pattern. Consumption of scalloped chicken was significantly associated with poisoning (OR = 4.488; p = 0.004; 95% CI: 1.544–13.049). All cases involved consumption of scalloped chicken. Laboratory tests showed drinking water containing Escherichia coli and total coliforms exceeding the threshold. The canteen's unhygienic conditions, proximity to a trash can, and abundance of flies support the possibility of cross-contamination. Conclusion: The outbreak is suspected to have been caused by contaminated chickens, with contributing factors including poor environmental sanitation and unsuitable water quality.